A study on the relationship between dementia partner nursing students' knowledge and attitudes on dementia - Lee, Hyunjung (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to assess the level of knowledge and attitudes toward dementia among Korean nursing students who completed dementia partner training, thereby providing baseline data for the development and implementation of dementia prevention education and programs. The participants were 308 nursing students who had completed dementia partner training, and the collected data were analyzed using SPSS 25.0. The subjects' dementia knowledge level was 9.91±2.02/15, and their dementia attitudes were 50.42±4.94/60. Dementia attitude scores differed significantly by gender and volunteer experience with dementia patients before the training. Females had significantly higher dementia attitude scores than males (t=-3.665, p<.001), and those with prior volunteer experience with dementia patients had significantly higher dementia attitude scores than those without (t=2.845, p=.005). A positive correlation was found between dementia knowledge and dementia attitudes (r=.205, p=.001). In conclusion, it is believed that various programs need to be developed, and various national policies need to be implemented to cultivate knowledge and attitudes about dementia.